A study on semantic and pragmatic features of idioms containing words denoting colors in English and Vietnamese - Ngô, Hoàng Ry. (ĐHĐN., 2014)
This thesis aims to investigate the semantic and pragmatic features of idioms containing words denoting color in English and Vietnamese. The study focuses on idioms containing color word in both languages in term of sematic and pragmatic – the two useful and effective methods widely used in linguistic to discover and understand the meaning of words. The data were extracted from books, newspapers, websites, dictionaries and other sources. 100 English idioms and 100 Vietnamese ones containing word denoting colors are investigated in this thesis. The study examined the semantic and pragmatic features of Idioms containing color word in English and Vietnamese basing on the following aspects: Firstly, the semantic and pragmatic feature of such kind of this idioms. Secondly, the semilarities and differences about idioms containing words denoting color cognition, culture as well as the use of languages. Revealved results can help us to understand why there are those similarities and differences. Furthermore, this thesis also makes some suggestions about useful ways to learn idioms containing color word sothat the learners not only comprehend but also use them properly